Changes in hepatic fibrosis stages after achieving SVR following direct‐acting anti‐viral treatment: a prospective study. Issue 1 (17th February 2020) - Shiha, Gamal; Soliman, Reham; Mikhail, Nabiel; Ibrahim, Alaa; Serwah, Abdel‐Hamid; Khattab, Mahmoud
Summary: Introduction: Chronic hepatitis C (CHC) represents a major global health problem. The availability of direct‐acting anti‐virals (DAAs) allowed the treatment of many patients with liver cirrhosis (F4) and advanced hepatic fibrosis (F3). The impact of viral clearance following DAAs treatment on the natural history of liver cirrhosis is uncertain or not clearly evident in the literature as most studies were retrospective, including small number of patients and for short follow‐up duration; there is a need for a long follow‐up, large prospective study evaluating the changes in hepatic fibrosis after achieving sustained virological response (SVR) in cirrhotics. Patients and methods: This is a prospective study including CHC patients with liver cirrhosis or advanced hepatic fibrosis who achieved SVR following DAAs from January 2015 until August 2017. Patients were followed up every 4‐6 months for at least 1 year from end of treatment. Staging of liver fibrosis was done using transient elastography and non‐invasive scores (FIB‐4, FIB‐5 and APRI). Results: A total of 2326 CHC patients who achieved SVR were included. Follow‐up period was 23.51 ± 8.21 months (range 12‐45). In cirrhotic patients, 21.8% showed reversal of cirrhosis, 27.4% showed fibrosis regression while 50.8% remained stationary. About 26.5% of F3 patients showed reversal of fibrosis, 31.5% showed fibrosis regression and 30.6% remained stationary while 11.4% progressed to F4. Conclusion: HCV clearance following DAAs treatment in CHC patients with liver cirrhosis or advanced hepatic fibrosis is associated with reversal of cirrhosis and regression of hepatic fibrosis in about 50% of patients.